2017
DOI: 10.1002/advs.201600416
|View full text |Cite
|
Sign up to set email alerts
|

Plants and Light Manipulation: The Integrated Mineral System in Okra Leaves

Abstract: Calcium oxalate and silica minerals are common components of a variety of plant leaves. These minerals are found at different locations within the leaf, and there is little conclusive evidence about the functions they perform. Here tools are used from the fields of biology, optics, and imaging to investigate the distributions of calcium oxalate, silica minerals, and chloroplasts in okra leaves, in relation to their functions. A correlative approach is developed to simultaneously visualize calcium oxalates, sil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 50 publications
1
37
0
Order By: Relevance
“…In many cases, the cystolith is connected to the outer cell wall through an internal silica stalk that helps to stabilize the ACC phase (Setoguchi et al, 1989;Sugimura et al, 1999;Gal et al, 2010Gal et al, , 2012b. It has been demonstrated that, in the palisade mesophylls of Ficus microcarpa, Morus alba, Abelmoschus esculentus (okra), and Peperomia obtusifolia, cystoliths or calcium oxalates function as light scatterers, increasing the leaf photosynthetic yield (Kuo-Huang et al, 2007;Detmann et al, 2012;Gal et al, 2012a;Horner, 2012;Horner et al, 2012;Pierantoni et al, 2017). Furthermore, in okra, the locations of calcium oxalate and silica deposits are not independent.…”
mentioning
confidence: 99%
“…In many cases, the cystolith is connected to the outer cell wall through an internal silica stalk that helps to stabilize the ACC phase (Setoguchi et al, 1989;Sugimura et al, 1999;Gal et al, 2010Gal et al, , 2012b. It has been demonstrated that, in the palisade mesophylls of Ficus microcarpa, Morus alba, Abelmoschus esculentus (okra), and Peperomia obtusifolia, cystoliths or calcium oxalates function as light scatterers, increasing the leaf photosynthetic yield (Kuo-Huang et al, 2007;Detmann et al, 2012;Gal et al, 2012a;Horner, 2012;Horner et al, 2012;Pierantoni et al, 2017). Furthermore, in okra, the locations of calcium oxalate and silica deposits are not independent.…”
mentioning
confidence: 99%
“…Notably, both of these properties were found to be highly correlated with one another, reporting on the wasted portion of absorbed light and therefore serving as an inverse proxy for the efficiency of photosynthesis (Govindjee 1986, Papageorgiou 2007). Measurement of chlorophyll fluorescence has the advantage of accessing local differences in fluorescence with micrometer resolution, and was used in two follow-up studies on various Ficus species (Pierantoni et al 2017, 2018). Microfluorimetry can thus be used to differentiate between the effects of irradiance on minerals and on the surrounding tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Scanning electron microscopy (SEM) has brought great revolution in the diversified fields of biological sciences and other disciplines during the last few decades (Esfandani‐Bozchaloyi & Zaman, , Luqman et al, ; Pierantoni et al, ; Ullah et al, Ullah et al, , Ullah et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Morphological and anatomical significance of wild fruits cannot be ignored because they have important characters that differentiate them from cultivated fruits and this information could be helpful in correct identification of the species, which is important in plant breeding techniques to improve the fruit production and taste for the growing population. Anticlinal wall pattern, stomata type, and stomatal aperture and orientation are the taxonomically useful cuticular features of plants which are helpful to distinguish a plant from other related taxa within a family (Kadiri, Asekun, & Olowokudejo, 2019 during the last few decades (Esfandani-Bozchaloyi & Zaman, 2018, Luqman et al, 2019Pierantoni et al, 2017;.…”
mentioning
confidence: 99%